Persistence of passive immunity in calves receiving colostrum from cows vaccinated with a live attenuated lumpy skin disease vaccine and the performance of serological tests - Rittipornlertrak, Amarin; Modethed, Wittawat; Sangkakam, Kanokwan; Muenthaisong, Anucha; Vinitchaikul, Paramintra; Boonsri, Kittikorn; Pringproa, Kidsadagon; Punyapornwithaya, Veerasak; Kreausukon, Khwanchai; Sthitmatee, Nattawooti; Singhla, Tawatchai (Frontiers in Veterinary Science, 2024)
This study aimed to determine the persistent duration of maternal immunity against lumpy skin disease virus (LSDV) in dairy calves born from vaccinated cows using a virus neutralization test (VNT). The performance of the VNT and an in-house-ELISA test was also determined. Thirty-seven pregnant cows from 12 LSD-free dairy farms in Lamphun province, Thailand were immunized with a homologous Neethling strain-based attenuated vaccine and calved from December 2021 to April 2022. Blood samples from dam-calve pairs were collected within the first week after calving. Subsequently, blood samples were taken from the calves at monthly intervals over a period of four months and tested for the humoral immune response using a VNT. The calf sera were also tested with an in-house ELISA test to estimate the accuracy of both tests using a Bayesian approach. For the results, antibodies against LSDV can persist in cows for 4-9 months post-vaccination. Moreover, neutralizing antibodies and LSDV-specific antibodies against LSDV were detected in the majority of calves (75.68%) during the first week after colostrum intake. However, the percentage of seropositive calves declined to zero by day 120, with seropositivity dropping below 50% after day 60. Only a small number of seropositive calves (approximately 13.51%) were observed on day 90. These findings indicated that passive immunity against LSDV can last up to three months. The median of posterior estimates for sensitivity (Se) and specificity (Sp) of the VNT were 87.3% (95% posterior probability interval [PPI] = 81.1-92.2%) and 94.5% (95% PPI = 87.7-98.3%), respectively. The estimated Se and Sp for the ELISA test were 83.1% (95% PPI = 73.6-92.6%) and 94.7% (95% PPI = 88.4-98.5%), respectively. In conclusion, this study illustrates the transfer and persistence of maternal passive immunity against LSDV to calves under field conditions. This highlights a potential three-month vaccination gap in calves born from vaccinated cows, while an in-house ELISA test can be used as an ancillary test for LSDV immune response detection. However, further research is required to assess the vaccination protocols for calves as young as two months old to precisely determine the duration of maternal immunity.